Pengaruh Penambahan Kitosan Terhadap Kualitas Bioplastik Biodegredable Berbahan Dasar Pati Jagung - Mochammad Rizki Fajri; Dewi Anggraini Septaningsih; Dea Dwi Ananda; Hazzha Azzahra; Latisa Stefi Alivia; Defandio Putra Gemilang Argiansyah; Farelino Oktavianus Purba; Wikrama Sarweswara (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The issue of non-degradable plastic waste has become a major concern, encouraging the development of environmentally friendly bioplastics based on natural materials. This study aims to synthesize and characterize chitosan derived from green mussel shells and apply it in the production of corn starch-based bioplastics, as well as to analyze the effect of chitosan addition on mechanical properties and water absorption. The method includes chitosan isolation through demineralization, deproteinization, and deacetylation, followed by bioplastic synthesis using the blending method. Characterization was carried out through organoleptic testing, yield calculation, ninhydrin test, biodegradability test, and water absorption test. The results show that the produced chitosan has good quality with a yield of 66.905% and a positive response to the ninhydrin test. The resulting bioplastic exhibits high biodegradability, indicated by significant degradation within two days. The addition of chitosan enhances structural strength and biodegradability but also increases water absorption and reduces flexibility. Overall, chitosan plays an important role in improving bioplastic performance, although composition optimization is required to achieve balanced material properties